Inventory Planning and Control in Perishable Items Products Using the Single Order Quantities Method (Case Study: PT XYZ) - Tanuwijaya, Amelia Tasya; Nurhasanah, Nunung; Tripiawan, Wawan (Universitas Al Azhar Indonesia, 2025)
Effective inventory management is crucial for companies distributing perishable products. PT XYZ requires a precise control method to optimize inventory and minimize losses. This study aims to determine the top 5 priority products, identify the best forecasting method with the smallest error and analyze the implementation of Single Order Quantities (SOQ) in inventory management. Using primary and secondary data collected from 1 January 2021 to 4 April 2022, the study employed ABC Analysis to categorize products, followed by demand forecasting using Single Moving Average, Single Exponential Smoothing, and Fuzzy Time Series to select the most accurate method. Inventory planning was then carried out using SOQ to enhance efficiency. Among 196 vegetable types, 5 were identified as the highest priority: Birdseye Chili Pepper (1 kg), Red Cayenne Pepper (1 kg), Birdseye Chili Pepper (Min. 5 kg), Local Cucumber (1 kg), and Bulk Green Paprika. The SOQ method enabled optimized inventory strategies, ensuring product availability while minimizing excess stock. This research provides practical insights for effective inventory planning, particularly for businesses handling perishable goods.Keywords - Demand Planning, Fuzzy Time Series, Inventory Planning, Perishable Product, Single Order Quantity.